Field‐aligned currents in Saturn's magnetosphere: Local time dependence of southern summer currents in the dawn sector between midnight and noon. Issue 8 (25th August 2016) - Hunt, G. J.; Cowley, S. W. H.; Provan, G.; Bunce, E. J.; Alexeev, I. I.; Belenkaya, E. S.; Kalegaev, V. V.; Dougherty, M. K.; Coates, A. J.
Abstract: We examine and compare the magnetic field perturbations associated with field‐aligned ionosphere‐magnetosphere coupling currents at Saturn, observed by the Cassini spacecraft during two sequences of highly inclined orbits in 2006/2007 and 2008 under late southern summer conditions. These sequences explore the southern currents in the dawn‐noon and midnight sectors, respectively, thus allowing investigation of possible origins of the local time (LT) asymmetry in auroral Saturn kilometric radiation (SKR) emissions, which peak in power at ~8 h LT in the dawn‐noon sector. We first show that the dawn‐noon field data generally have the same four‐sheet current structure as found previously in the midnight data and that both are similarly modulated by "planetary period oscillation" (PPO) currents. We then separate the averaged PPO‐independent (e.g.,  subcorotation) and PPO‐related currents for both LT sectors by using the current system symmetry properties. Surprisingly, we find that the PPO‐independent currents are essentially identical within uncertainties in the dawn‐dusk and midnight sectors, thus providing no explanation for the LT dependence of the SKR emissions. The main PPO‐related currents are, however, found to be slightly stronger and narrower in latitudinal width at dawn‐noon than at midnight, leading to estimated precipitating electron powers, and hence emissions, that are on average a factor of ~1.3 larger at dawn‐noon than at midnight, inadequate to account for the observed LT asymmetry in SKR power by a factor of ~2.7. Some other factors must also be involved, such as a LT asymmetry in the hot magnetospheric auroral source electron population. Key Points: We examine the LT dependence of Saturn's southern field‐aligned currents in the dawn sector Only modest differences are found between the mean currents in the midnight and dawn‐noon sectors The differences are insufficient to explain the peak in radio emissions in the dawn‐noon sector